Fully Transparent, Ultrathin Flexible Organic Electrochemical Transistors with Additive Integration for Bioelectronic Applications (Adv. Sci. 2/2023). Issue 2 (13th January 2023) - Takemoto, Ashuya; Araki, Teppei; Nishimura, Kazuya; Akiyama, Mihoko; Uemura, Takafumi; Kiriyama, Kazuki; Koot, Johan M.; Kasai, Yuko; Kurihira, Naoko; Osaki, Shuto; Wakida, Shin‐ichi; den Toonder, Jaap M.J.; et al.
Abstract : Flexible Organic Electrochemical Transistors In article number 2204746, Teppei Araki, Tsuyoshi Sekitani, and co‐workers develop fully transparent and ultra‐thin, and flexible organic electrochemical transistors using additive manufacturing process that reduces damage to nanomaterials. Integrated biosensors using the transistors can provide multimodal assessments such as electrophysiological, optical and ion measures, and are holding promises toward complex point‐of‐care diagnosis of human stress.